Stereoselective metabolism of chloramphenicol by bacteria isolated from wastewater, and the importance of stereochemistry in environmental risk assessments for antibiotics. (15th June 2022) - Elder, Felicity C T; Pascoe, Ben; Wells, Stephen; Sheppard, Samuel K; Snape, Jason; Gaze, William H; Feil, Edward J; Kasprzyk-Hordern, Barbara
Highlights: Stereoselective metabolism of chloramphenicol (CAP) by wastewater bacteria investigated. Chloramphenicol acetyltransferase (CAT) stereoselectively transformed CAP. Only RR- and RS-CAP were transformed into chloramphenicol acetate. Stereochemistry around the first stereocentre is key for CAT recognition. ERA needs to acknowledge stereochemistry of antibiotics. Abstract: Wastewater treatment plants have been highlighted as a potential hotspot for the development and spread of antibiotic resistance. Although antibiotic resistant bacteria in wastewater present a public health threat, it is also possible that these bacteria play an important role in the bioremediation through the metabolism of antibiotics before they reach the wider environment. Here we address this possibility with a particular emphasis on stereochemistry using a combination of microbiology and analytical chemistry tools including the use of supercritical-fluid chromatography coupled with mass spectrometry for chiral analysis and high-resolution mass spectrometry to investigate metabolites. Due to the complexities around chiral analysis the antibiotic chloramphenicol was used as a proof of concept to demonstrate stereoselective metabolism due to its relatively simple chemical structure and availability over the counter in the U.K. The results presented here demonstrate the chloramphenicol can be stereoselectively transformed by the chloramphenicol acetyltransferase enzyme with the orientation around the first stereocentre being key for this process, meaning that accumulation of two isomers may occur within the environment with potential impacts on ecotoxicity and emergence of bacterial antibiotic resistance within the environment. Graphical Abstract: Graphical Abstract Image, graphical abstract .